Primary extraskeletal duodenal osteosarcoma with peritoneal sarcomatosis in a cat - Fabian Z.X. Lean; Benjamin J. Haythornthwaite; Sophie E. Broughton; Jodie R. Green; Francisco Llabres-Diaz; Balazs Szladovits; Henny M. Martineau (Journal of Comparative Pathology, 2025)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Egg retention of high-latitude sockeye salmon (Oncorhynchus nerka) in the Pilgrim River, Alaska, during the Pacific marine heatwave of 2014–2016 - Michael P. Carey; Vanessa R. von Biela; Ashley Dunker; Kevin D. Keith; Merlyn Schelske; Charlie Lean; Christian E. Zimmerman (Polar Biology, 2021)

COVID-19: the impact of a global crisis on sustainable development research - Walter Leal Filho; Anabela Marisa Azul; Tony Wall; Claudio R. P. Vasconcelos; Amanda Lange Salvia; Arminda do Paço; Kalterina Shulla; Vanessa Levesque; Federica Doni; Lorena Alvarez-Castañón; Claudia Mac-lean; Lucas Veiga Avila; et al. (Sustainability Science, 2021)

Observations on the dynamics and fate of dissolved organic phosphorus in lake water and a new model of eplimnetic P cycling - William D. Taylor; David R. S. Lean (Aquatic Sciences, 2018)

A glossary for biometeorology - Simon N. Gosling; Erin K. Bryce; P. Grady Dixon; Katharina M. A. Gabriel; Elaine Y. Gosling; Jonathan M. Hanes; David M. Hondula; Liang Liang; Priscilla Ayleen Bustos Mac Lean; Stefan Muthers; Sheila Tavares Nascimento; Martina Petralli; et al. (International Journal of Biometeorology, 2014)

Environmental Factors Affecting Ultraviolet Photodegradation Rates and Estrogenicity of Estrone and Ethinylestradiol in Natural Waters - Susanna K. Atkinson; Vicki L. Marlatt; Lynda E. Kimpe; David R. S. Lean; Vance L. Trudeau; Jules M. Blais (Archives of Environmental Contamination and Toxicology, 2011)

Potential causes of enhanced transfer of mercury to St. Lawrence River Biota: implications for sediment management strategies at Cornwall, Ontario, Canada - J. J. Ridal; L. E. Yanch; A. R. Fowlie; N. R. Razavi; T. M. Delongchamp; E. S. Choy; M. Fathi; P. V. Hodson; L. M. Campbell; J. M. Blais; M. B. C. Hickey; E. Yumvihoze; et al. (Hydrobiologia, 2010)

Temporal Trends and Spatial Variability of Mercury in Four Fish Species in the Ontario Segment of the St. Lawrence River, Canada - Richard R. Goulet; J. D. Lalonde; F. Chapleau; S. C. Findlay; D. R. S. Lean (Archives of Environmental Contamination and Toxicology, 2008)

Seasonal and Inter-Annual Variations in Methyl Mercury Concentrations in Zooplankton from Boreal Lakes Impacted by Deforestation or Natural Forest Fires - Edenise Garcia; Richard Carignan; David R. S. Lean (Environmental Monitoring and Assessment, 2007)

Use of Comet and Micronucleus Assays to Measure Genotoxicity in Meadow Voles (Microtus pennsylvanicus) Living in Golf Course Ecosystems Exposed to Pesticides - Loren D. Knopper; Pierre Mineau; James P. Mcnamee; David R. S. Lean (Ecotoxicology, 2005)

Physical and chemical limnology of northern boreal lakes, Wood Buffalo National Park, northern Alberta and the Northwest Territories, Canada - K. A. Moser; J. P. Smol; D. R. S. Lean; G. M. MacDonald (Hydrobiologia, 1998)

Limnological characteristics of lakes located across arctic treeline in northern Russia - Katharine E. Duff; Tamsin E. Laing; John P. Smol; David R. S. Lean (Hydrobiologia, 1998)

Implications of ozone depletion for surface-water photochemistry: Sensitivity of clear lakes - Norman M. Scully; Warwick F. Vincent; David R. S. Lean; William J. Cooper (Aquatic Sciences, 1997)

Implications of ozone depletion for surface-water photochemistry: Sensitivity of clear lakes - Norman M. Scully; Warwick F. Vincent; David R. S. Lean; William J. Cooper (Aquatic Sciences, 1997)

Pelagic food web interactions and hypolimnetic oxygen depletion: Results from experimental enclosures and lakes - Asit Mazumder; D. J. McQueen; W. D. Taylor; D. R. S. Lean (Aquatic Sciences, 1990)